2018
DOI: 10.1111/mec.14464
|View full text |Cite
|
Sign up to set email alerts
|

microRNA regulation in an ancient obligate endosymbiosis

Abstract: Although many insects are associated with obligate bacterial endosymbionts, the mechanisms by which these host/endosymbiont associations are regulated remain mysterious. While microRNAs (miRNAs) have been recently identified as regulators of host/microbe interactions, including host/pathogen and host/facultative endosymbiont interactions, the role miRNAs may play in mediating host/obligate endosymbiont interactions is virtually unknown. Here, we identified conserved miRNAs that potentially mediate symbiotic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 90 publications
(180 reference statements)
2
45
0
Order By: Relevance
“…In addition, A. pisum has two Rag A/B, and Skp2 orthologs, and M. persicae two Nup44A orthologs. All of these duplicated genes with the exception of the two RHEB orthologs unique to A. pisum are detected in wingless parthenogenetic female aphid transcriptomes (Feng et al 2018; NCBI BioProject PRJNA315109). The two RHEB orthologs unique to A. pisum were not detected in the transcriptomes associated with this study but are found in an alate male aphid transcriptome (data from Jaquiéry et al , 2018.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, A. pisum has two Rag A/B, and Skp2 orthologs, and M. persicae two Nup44A orthologs. All of these duplicated genes with the exception of the two RHEB orthologs unique to A. pisum are detected in wingless parthenogenetic female aphid transcriptomes (Feng et al 2018; NCBI BioProject PRJNA315109). The two RHEB orthologs unique to A. pisum were not detected in the transcriptomes associated with this study but are found in an alate male aphid transcriptome (data from Jaquiéry et al , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence for a host-catalyzed final step of branched chain amino acid biosynthesis supports intimate coordination between the aphid and Buchnera in completion of amino acid biosynthesis pathways (Hansen and Moran 2011), but also opens the metabolic pathway to host control. Recent work identifying microRNA (miRNA) targets in aphid bacteriocytes suggests that expression of BCAT is miRNA regulated, thereby implicating host regulatory checks in the production of the branched-chain amino acids (Feng et al 2018). With respect to symbiont control, it is of interest that the genes for leucine biosynthesis are located on a plasmid within Buchnera from M. persicae and A. pisum , a genomic location that potentially uncouples leucine production rates from Buchnera genome copy number, a feature of symbiont genome evolution that possibly reveals some level of endosymbiont control of leucine production (Baumann et al 1999; Jiang et al 2013; Shigenobu et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations